Relationship between Supportive Supervision and Caring Behavior among Healthcare Workers: The Mediating Role of Job Satisfaction - Edosomwan, Henry Samuel; Nwanzu, Chiyem Lucky; Omreore, Obaro Efficiency (International Journal of Occupational Safety and Health, 2024)
Introduction: Healthcare workers are tasked with ensuring that patient needs are well taken care of and managed as it relates to specific health challenges. A significant way of ensuring the efficacy of treatment is through human interaction with a focus on caring behavior. There are few studies examining factors within the health sector and their impact on the caring behavior of healthcare workers. Accordingly, this study examined the mediating role of job satisfaction in the relationship between supportive supervision and caring behavior among healthcare workers in the public sector. Methods: A quantitative method of collecting data via the cross-sectional design was adopted. Simple and convenient sampling techniques were used in the study. Simple random sampling was adopted for selecting the public hospitals while convenience sampling was used for selecting the participating healthcare workers. Three standardized self-report instruments with good psychometric properties were used for collecting the data. A regression-based analysis (complemented with PROCESS Macro v4.2) was used for testing the hypotheses through the IBM SPSS v25. Results: The participants consisted of 204 healthcare workers currently working in publicly owned hospitals in Delta State, Nigeria. The sample consisted of 97(47.5%) males and 107(52.5%) females with mean age of 40.74years (SD= ±8.877). The results of the study provided support for the four hypotheses that were tested. Supportive supervision (b= .19, t = 3.10, p < .01) and job satisfaction (b= .11, t = 4.33, p < .001) positively and significantly predicted caring behaviour. Also, supportive supervision (b= .33, t = 2.19, p < .05) positively and significantly predicted job satisfaction while job satisfaction mediated the relationship between supportive supervision and caring behavior. Conclusion: This study demonstrates the importance of supportive supervision and job satisfaction in predicting the caring behavior of healthcare workers in Delta State, Nigeria. Consequently, it is recommended that policymakers, hospital administrators, and practitioners in the health sector put in place frameworks that will promote supportive supervision and job satisfaction.